Adenoid cystic carcinoma of palate: A unique case report - Mainak Datta; Rupam Sinha; Soumyabrata Sarkar; Sayani Shome (Wolters Kluwer Medknow Publications, 2022)
Adenoid cystic carcinoma (ADCC) is one of the malignant salivary gland neoplasm and constitutes for 1% of head and neck malignancies and 22% of all salivary gland malignancies. Palate is the most common site to be involved in the oral cavity followed by parotid region, tongue, and floor of mouth. It is commonly seen in middle age population with slight female predilection. It usually appears as asymptomatic, slow growing infiltrative growth with high recurrence, often presence of perineural invasion which appears as pain. In this present case of ADCC, a 65-year-old female patient reported with a swelling on the left side of hard palatal area since 3 months with occasional pain and history of epistaxis, which was diagnosed clinically, radiographically, and histopathologically and confirmed by immunohistochemistry as Grade III solid variety of ADCC with a poor prognosis.